Particle embolization of the bilateral superior and inferior alveolar arteries for life threatening dental socket hemorrhage. (9th August 2011) - Pham, Nancy; Sivapatham, Thinesh; Hussain, Muhammad S; Bhalla, Tarun; Masaryk, Thomas J; Hui, Ferdinand K
Abstract : Particle embolization for epistaxis and intra-oral hemorrhage are performed on an as needed basis by neurointerventionalists. A case is presented of massive oral hemorrhage associated with end stage liver disease coagulopathy after tooth extraction of bilateral maxillary and mandibular molars. A man in his fifties with end stage liver disease who presented for evaluation of a syncopal episode was determined to be in hemorrhagic shock from 2 days of persistent oral bleeding after elective tooth extractions. Conservative management with multiple blood transfusion products, packing and vasoconstrictive spray was ineffective. Microcatheter angiograms of the alveolar arteries demonstrated blood and contrast pooling within the sockets of the extracted teeth. Selection of the bilateral supplying alveolar and inferior alveolar artery branches was achieved followed by polyvinyl alcohol particle embolization (250–355 μm). Polyvinyl alcohol particle embolization of dental socket hemorrhages is technically feasible and effective.